139k views
3 votes
11h-5(h+3)=-63 find they value of h

User Runeh
by
5.0k points

2 Answers

0 votes

Answer:

Explanation:

11h - 5(h + 3) = -63

-Multiply parenthesis so

-5(h) + -5(3) = -5h - 15

New equation: 11h - 5h - 15= -63

+15 +15

(add 15 to both sides)


6h=-48\\\\(6h)/(6) =(-48)/(6) \\ \\ h=-8

h = -8

User LambdaBeta
by
5.4k points
4 votes

Answer:

h = -13

Explanation:

Use PEMDAS to solve this problem.

11h - 5(h + 3) = -63

~Use distributive property to simplify [ a(b + c) = ab + ac ]

11h - 5h + 15 = -63

~Combine like terms

6h + 15 = -63

~Subtract 15 to both sides

6h = -78

~Divide 6 to both sides

h = -13

Best of Luck!

User Jokkedk
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.